Should we ditch impact factors? - Williams, Gareth (BMJ Publishing Group Ltd., 2007)
Even advocates of impact factors admit that they are a flawed measure of quality. Gareth Williams believes we should get rid of them whereas Richard Hobbs thinks refinement is the answer